Characterization of compliance to weight-bearing protocols and patient weight-bearing behavior during the recovery period in lower extremity fractures: a pilot study. Issue 4 (July 2019) - Lajevardi-Khosh, Arad; Stuart, Ami; Ackerman, Matt; Rothberg, David; Kubiak, Erik; Petelenz, Tomasz; Hitchcock, Robert
Abstract : Background: To promote fracture healing and limit complications, clinicians typically instruct patients with lower extremity fracture to be nonweight or partial-weight bearing or to bear weight as tolerated during the recovery period. Although this practice represents the standard of care, continuous patient compliance to weight-bearing protocols and actual patient weight-bearing progression remain unknown. This study aimed to characterize patient compliance towards weight-bearing protocols and weight-bearing progression during recovery. Methods: Eleven patients with lower extremity fracture consented to participate in this observational study. Postoperatively, patients were instructed to follow weight-bearing protocols based upon the treating clinicians' recommendation. Patients were fitted with an underfoot load monitor integrated into the sole of a walking boot. Continuous load data from each patient were used to quantify the number of days patients were compliant with the weight-bearing protocol. Results: Overall, patients were unable to comply to nonweight-bearing and partial-weight-bearing protocols. Patients performed nonweight bearing and partial weight bearing only 24% and 12% of the time, respectively. Patients were most compliant (72%) to the weight bearing as tolerated protocol. Additionally, weight-bearing progressions either consistently increased (46%), remained relatively constant (27%), or remained constant initially and then suddenly increased (27%). Conclusions: Continuous compliance data from this study indicate that patients do not comply with weight-bearing protocols. Additionally, the variety of weight-bearing progressions, with limited complications, may suggest that patients are able to self-regulate their weight bearing without compromising healing outcomes.